The role of intergenerational support in shaping oral healthcare-seeking behavior among older adults in China - Wen, Cai; Zhang, Qing (Frontiers in Public Health, 2023)
Background This study aimed to explore how intergenerational support affects the oral healthcare or treatment-seeking behaviors of older Chinese adults and provide evidence for improving the oral health of the older adults in an aging society. Methods Data from a cross-sectional survey, the 2015 China Health and Retirement Longitudinal Study, were used to explore the relationship between oral healthcare-seeking behavior in older adults and various independent variables, such as marital status, number of children, offspring’s education duration, parent–offspring interaction frequency, and financial/material support provided by children. The chi-square test and binary logistic regression were used. Results According to the results of data analysis, age, sex, marital status, cohabitation status, number of children, children’s education level, and financial support from children affected older adults’ oral healthcare-seeking behavior. Interviewees living with a partner and those who had 1–2 or 3–4 children showed different likelihoods of seeking oral healthcare. Moreover, interviewees whose children had higher education duration and those who received more financial/material support from their children were more likely to seek dental treatment. Conclusion Regarding the study’s outcome, financial and emotional support, as well as practical assistance from family members can significantly promote oral health-seeking behavior among older adult people. Intergenerational support can serve as a crucial mechanism for promoting oral health behaviors among the older adults or act as a valuable complement to social medical assistance, warranting increased attention.